Branding Kopi Single Origin Kayumas: Upaya Petani Kopi Memasarkan Produk Kopi Arabika Desa Kayumas Situbondo - Sampurna, Insan Cita; Suciati, Luh Putu; Subekti, Sri (Universitas Galuh, 2024)
The research on the branding of Kayumas single origin coffee as an effort by coffee farmers in Kayumas Village to market Arabica coffee products is intriguing to explore. Despite having the